Evaluation of water and paraffin PCM as storage media for use in thermal energy storage applications: A numerical approach. (February 2020) - Pagkalos, Christos; Dogkas, George; Koukou, Maria K.; Konstantaras, John; Lymperis, Kostas; Vrachopoulos, Michail Gr.
Abstract: Two different heat storage media, namely water and paraffin phase change material, are studied in order to evaluate and compare them for use in thermal energy storage systems. Using commercial computational fluid dynamics software, the charging process of the two materials is simulated and the results focus on the energy stored, the storage material temperature and heat transfer fluid outlet temperature. The geometric characteristics of the computational domain are selected in accordance with commercially used heat exchangers for thermal storage applications. Two different tube lengths and two different feed rates are used for the comparison of the charging process, while the heat transfer fluid temperature and the initial temperature of the components of the system are the same for all the simulations. Results show that for the same volume of storage mediums, the phase change material can store more energy than water, for the same temperature of the heat transfer fluid, as expected. As the feed rate is doubled, the same energy is stored in the media, but in approximately half the time. The simulation yielded an increase of the storage capacity of the examined system by approximately 4.1 times when phase change material is used instead of water and a significantly lower storage medium temperature change during the process. It is also shown that the stored energy is about 6.6 times greater for the 6.6 m long tube than the 1 m long tube and is proportional to the heat storage medium mass. However, the duration of the process is not proportional to the heat storage medium mass and when using water as heat storage medium, it almost doubles for a 6.6 times longer tube, while when using phase change material the duration increases approximately only 1.5 times.